Influential factors of urinary arsenic levels in the population residing close to one heavy-industrial area in Taiwan - A case study - Kaewlaoyoong, Acharee; Huang, Shih-Ting; Wang, Shu-Li; Sun, Chien-Wen; Chen, Jia-Jen; Kuo, Chao-Hung; Hung, Chih-Hsing; Chen, Szu-Chia; Liang, Ching-Chao; Tsai, Hsiao-Wen; Wu, Chia-Fang; Lin, Wen-Yi; et al. (Frontiers in Environmental Science, 2022)
The public in southwestern Taiwan’s Kaohsiung City have expressed concern over risk of arsenic (As) to people living in six villages of that city nearby a coastal heavy-industrial area. To investigate, we first analyzed urinary total As (TAs) levels in 328 adult subjects from the Nutrition and Health Survey in Taiwan in 2005-2008 (NAHSIT 2005-8). We found the top three highest median urinary TAs levels in residents from the Penghu islands (150.90 µg/L, n = 21) and the upper northern region (78.04 µg/L, n = 56) and the southern region (75.21 µg/L, n = 33) of Taiwan. Then, urinary TAs levels in 1,801 and 1,695 voluntary adult residents of the above-mentioned six villages in 2016 and 2018 respectively were compared with those from the top three highest TAs levels of NAHSIT 2005-8. Median urinary As levels were 84.60 µg/L in 2016 and 73.40 µg/L in 2018, similar to those in the southern region of Taiwan, but far below those in the Penghu islands (p <0.05). Finally, in 2020, we interviewed 116 healthy adult residents from the same six villages and analyzed one-spot urine samples of total inorganic-related As (TiAs), a summation of As3+, As5+, monomethylarsonic acid, and dimethylarsinic acid. Subjects consuming seafood two days before urine sampling (n = 15) were significantly higher TiAs levels than those not (n = 101, p = 0.028). These findings suggest that seafood consumption is probably the main source of urinary TAs and TiAs in people residing close to that coastal heavy-industrial area.